Who Am I: The Conscious and the Unconscious Self - Schaefer, Michael; Northoff, Georg (Frontiers in Human Neuroscience, 2017)
Who am I? What is the self and where does it come from? This may be one of the oldest problems in philosophy. Beyond traditional philosophy, only very recently approaches from neuroscience (in particular imaging studies) have tried to address these questions, too. So what are neural substrates of our self? An increasing body of evidence has demonstrated that a set of structures labeled as cortical midline structures are fundamental components to generate a conscious self. Moreover, recent theories on embodied cognition propose that this conscious self might be supplemented by additional structures, for example, in the somatosensory cortices, which enable our brain to create an ‘embodied mind’. While the self based on cortical midline structures may be related to a conscious self, we here propose that the embodied facet of the self may be linked to something we call unconscious self. In this article we describe problems of this model of a conscious and unconscious self and discuss possible solutions from a theoretical point of view.